PIMPIN organised Amazing al-Quran Seminar - UMP, PNC (2019)
Islamic Centre & Human Development (PIMPIN), Universiti Malaysia Pahang (UMP) organised the Amazing al-Quran seminar which was held in conjunction with the Nuzul al-Quran Day at Tun Fatimah Hall, UMP Gambang Campus on April 15, 2019.